(untitled) - Phillips, Terry (Vietnam, 2013)
This course will help you improve your competence in the basic skills of English for college or university study. In Starting Skills Book 2 you will learn 200 key words from ten knowledge areas. You will also learn to: * define and describe objects * identify key factual information * predict information in a talk * talk about charts and graphs * discuss key facts in the past * identify key parts of speech * read factual information and encyclopedia entries * write accurately using basic sentence patterns * use key spelling rules
Keywords: English language,Tiếng Anh; Problems, exercises, etc,Câu hỏi và bài tập